Genetic Separation of the Inosinic Acid Cyclohydrolase-Transformylase Complex of Salmonella typhimurium - Gots, Joseph S. (1969)
Genetic and enzymatic analyses were made with the purH mutants of Salmonella typhimurium. These mutants are purine auxotrophs which are deficient in the conversion of phosphoribosyl-aminoimidazolecarboxamide (AIC) to inosine-5′-monophosphate (IMP). Two steps are required for this process: phosphoribosyl-AIC transformylase (EC 2.1.2.3) and IMP cyclohydrolase (EC 3.5.4.10). Genetic analysis identified two complementation groups, I and II, and a third group of noncomplementing mutants (I–II). Mutations in gene I lead to complete loss of transformylase activity and no loss of cyclohydrolase activity if the mutation is of the missense type, but partial loss if it is of the chain-terminating type (nonsense or frameshift). Gene II mutants are all of the missense type and show normal transformylase activity but no cyclohydrolase activity. The noncomplementing mutants (I–II) are all of the chain-terminating type and are completely deficient in both activities. The results are explained and discussed in terms of subunit interactions of a stable enzyme complex.